Perancangan dan Implementasi Sistem Monitoring Amonia, Suhu, dan Kelembaban Pada Kandang Ayam Close House Berbasis Internet of Things - Rizaldi, falhan Febrian (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
The poultry industry with a closed-house system has experienced rapid growth, but controlling air quality, especially ammonia (NH3) gas, remains a challenge for farmers. In this research, the authors successfully designed and implemented an IoT-based monitoring system to monitor the air quality of chicken coops in real-time. The system is capable of measuring ammonia levels, temperature, and humidity. The system consists of three parts: node, master, and gateway. In the node section, there are MQ-135 and DHT11 sensors to measure ammonia, temperature, and humidity. Data processing from the sensors uses an ESP32 microprocessor and LoRa E32 module. The measurement results of the sensor are displayed on an LCD and website using Internet of Things technology. The results of this study show that this system is effective in monitoring ammonia levels, temperature, and humidity, thus helping farmers maintain air quality in coops and increase productivity. With this tool, farmers can monitor coop conditions in real-time and take necessary actions.